Community-Based Social Marketing Strategy in Kampung Cibunut Berwarna: Advancing Edutourism in a Sustainable Circular Economy - Hermawan, Daniel; Trivena Muabuai, Ribka; Angelica, Maria; Markus, Monica; Nurfatha, Dianajmi; Suryajaya Eltanto, Kevin; Salman Praja, Rinaldhi; Sariputta, Stephen (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
This paper proposes a community-based social marketing model and outlines its role and methodology in developing a sustainable circular economy within internal brand-building. It broadens community- based social marketing by incorporating diverse education tourism (edutourism) activities within a sustainable circular economy, extending beyond traditional literature. Adopting a case study using an open-ended phenomenological approach, we collected data through five in-depth interviews and a focus group discussion. The participants were community leaders and members engaged in sustainable circular economy development in Kampung Cibunut Berwarna, Bandung, Indonesia. Additionally, we analysed related documents, including archival records and descriptions of internal processes, to complement the primary data. The findings provide empirical insights into change mechanism in community-based social marketing. Notably, visionary leaders, the ripple effect of edutourism, and content as a branding emblem help integrate sustainable circular economy behaviour into edutourism. While this study provides valuable insights into the practices in the research site, the case study may limit generalisability to larger areas and different societal challenges. Future research should test these propositions in diverse geographical contexts.